1999
DOI: 10.1007/s000180050386
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and protein synthesis on the renaturation of firefly luciferase in intact H9c2 cells

Abstract: A mild increase in temperature that does not exert an effect on tolerance development or synthesis of heat shock proteins (Hsps) in control cells can stimulate these processes when applied to cells that have previously been heat shocked. To study the underlying mechanism of this effect, H9c2 cells were stably transfected with the gene encoding firefly luciferase (Luc). Heat-shock-induced inactivation of Luc and its subsequent reactivation is frequently used as a model for cellular protein denaturation and rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…Similar results were obtained for L. mingrelica luciferase (Lundovskikh et al, 1998;Ugarova et al, 2000). It was demonstrated that inactivated luciferase is virtually unable to restore activity after cooling and usually aggregates (Minami & Minami, 1999;Schumacher et al, 1996;Souren et al, 1999aSouren et al, , 1999b. Appreciable spontaneous reactivation was only observed for diluted solutions of luciferase that was fully inactivated by guanidine chloride.…”
Section: Stability Of Firefly Luciferases In Solutionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were obtained for L. mingrelica luciferase (Lundovskikh et al, 1998;Ugarova et al, 2000). It was demonstrated that inactivated luciferase is virtually unable to restore activity after cooling and usually aggregates (Minami & Minami, 1999;Schumacher et al, 1996;Souren et al, 1999aSouren et al, , 1999b. Appreciable spontaneous reactivation was only observed for diluted solutions of luciferase that was fully inactivated by guanidine chloride.…”
Section: Stability Of Firefly Luciferases In Solutionsupporting
confidence: 78%
“…Substrate and competitive inhibitors change the conformation of luciferase, when introduced to prokaryotic and eukaryotic cells, leading to a several-fold decrease of enzyme degradation (Thompson et al, 1991). P. pyralis luciferase quickly inactivates in eukaryotic cells at 40-45°C with a half-life of 4-20 min (Forreitor et al, 1997;Souren et al, 1999b). Nevertheless, the stability can be relatively high at moderate temperatures.…”
Section: Stability Of Firefly Luciferases In Solutionmentioning
confidence: 99%
“…1C). As luciferase protein denatures quickly after translation and loses enzymatic activity (50), the measure of enzymatic activity corresponds to active translation of encoded mRNA, suggesting that mRNA transfection of DC results in transient, high level protein production.…”
Section: Transfection Of DC With Mrna-encoding Reporter Proteinsmentioning
confidence: 99%
“…This finding is in complete agreement with previous studies that estimated the synthesis rate of luciferase to be 2.6% per hour relative to the basal amount of luciferase already present within a cell. 22,23 After miniaturizing the cancer cell-based assay to a 384-well format, the Z-factor and S/N observed were 0.5 and 7, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Others have described the use of luciferase as a reporter of chaperone activity in Arabidopsis and in the rat myoblast cell, H9c2. [21][22][23] Assays based on rabbit reticulocyte lysates have been successfully used to biochemically characterize the refolding kinetics of the Hsp70/Hsp90 system as well as a screening tool to identify compounds that inhibit Hsp90 activity. 24 While the rabbit reticulocyte assay is quite sensitive and robust, questions remain as to the physiological relevance of the active chaperone complexes in this system, as it represents a species more related to normal tissue rather than disease.…”
Section: Introductionmentioning
confidence: 99%